Weaknesses and difficulties of multiprofessional residence in health from the perspective of nursing: an experience report (Research, Society and Development, 2022)
Objective: to expose the weaknesses and difficulties observed by a nursing resident during his work in the hospital environment, of a multiprofessional residency in orthopedics and traumatology. Metodology: This research was a descriptive study, of the experience report type, carried out at the Surgical Clinic (CC) of a low and medium complexity hospital in the city of Santarém - Pará, from March to May of the year 2021. Results: The multiprofessional residency in health is a space for learning within the scope of work, even though it is an ideal environment to acquire knowledge and experience, the residency has several weaknesses that make it difficult for the resident professional in daily practice, such as: fragile tutoring, excessive workload, deficit of qualified tutors, lack of spaces for interaction, among others. Final Considerations: It was evidenced that during the training process there are still structural and organizational challenges, which in a way hamper the performance of resident professionals, with the need to restructure the programs already in place.